Incidence of human brucellosis in the Kilimanjaro Region of Tanzania in the periods 2007–2008 and 2012–2014. (25th April 2018) - Carugati, Manuela; Biggs, Holly M; Maze, Michael J; Stoddard, Robyn A; Cash-Goldwasser, Shama; Hertz, Julian T; Halliday, Jo E B; Saganda, Wilbrod; Lwezaula, Bingileki F; Kazwala, Rudovick R; Cleaveland, Sarah; Maro, Venance P; et al.
Abstract: Background: Brucellosis causes substantial morbidity among humans and their livestock. There are few robust estimates of the incidence of brucellosis in sub-Saharan Africa. Using cases identified through sentinel hospital surveillance and health care utilization data, we estimated the incidence of brucellosis in Moshi Urban and Moshi Rural Districts, Kilimanjaro Region, Tanzania, for the periods 2007–2008 and 2012–2014. Methods: Cases were identified among febrile patients at two sentinel hospitals and were defined as having either a 4-fold increase in Brucella microscopic agglutination test titres between acute and convalescent serum or a blood culture positive for Brucella spp. Findings from a health care utilization survey were used to estimate multipliers to account for cases not seen at sentinel hospitals. Results: Of 585 patients enrolled in the period 2007–2008, 13 (2.2%) had brucellosis. Among 1095 patients enrolled in the period 2012–2014, 32 (2.9%) had brucellosis. We estimated an incidence (range based on sensitivity analysis) of brucellosis of 35 (range 32–93) cases per 100 000 persons annually in the period 2007–2008 and 33 (range 30–89) cases per 100 000 persons annually in the period 2012–2014. Conclusions: We found a moderate incidence of brucellosis in northern Tanzania, suggesting that the disease is endemic and an important human health problem in this area.